Efficacy of Mediterranean diet in musculoskeletal disorders: A systematic review and meta-analysis for primary and tertiary prevention featured in the Italian National Guidelines "La Dieta Mediterranea". - Limongi, Federica; Cilona, Laura; Guberti, Emilia; Volpe, Massimo; Maggi, Stefania; Onder, Graziano; Silano, Marco; Zanetti, Michela; Sieber, Cornel; Gianfredi, Vincenza; Nucci, Daniele; Ragusa, Francesco Saverio; et al. (Nutrition, 2026)
OBJECTIVES: Musculoskeletal disorders (MSDs) represent a leading cause of disability. Given its anti-inflammatory and antioxidant properties, the Mediterranean diet (MD), may be a low-cost strategy for the prevention of MSDs. The aim of this systematic review and meta-analysis is to summarize the evidence and evaluate the association between adherence to the MD and prevention of MSDs. METHODS: This review was conducted in accordance with PRISMA 2020 and MOOSE guidelines. A comprehensive search of several databases was performed up to February 28, 2024. Study quality was assessed using the Newcastle-Ottawa Scale, and the certainty of evidence was evaluated using the NUTRIGRADE approach. Pooled effect sizes were computed using a random-effects model and expressed as risk ratios (RR), hazard ratios (HR), or odds ratios (OR), as appropriate. RESULTS: A total of 16 studies were included. Higher adherence to the MD was associated with a possible risk reduction in the prevalence of osteoporosis in adults (OR = 0.77; 95% confidence interval [CI]: 0.60-1.00; low degree of certainty). A one-point increase in MD adherence was associated with a slight reduction in the risk of incidence of fractures (RR = 0.97, 95% CI: 0.94-0.99) and in the risk of pain in patients with knee OA (HR = 0.98, 95% CI: 0.97-0.998), with a moderate degree of certainty. CONCLUSIONS: Adherence to the MD may exert some beneficial effects in the risk of incidence of fractures in the general population and in the risk of pain among patients with knee OA. However, more high-quality studies are needed.
EVALuna2:611061